2004
DOI: 10.1016/s0550-3213(04)00300-1
|View full text |Cite
|
Sign up to set email alerts
|

Two-loop SUSY corrections to the anomalous magnetic moment of the muon

Abstract: We calculate supersymmetric two-loop corrections to the anomalous magnetic moment of the muon, consisting of diagrams with a closed scalar fermion or fermion loop and gauge and/or Higgs boson exchange. We discuss the numerical impact of each subclass of diagrams and determine the leading contributions. We analyze in detail constraints from experimental information on the Higgs boson mass, ∆ρ, and the branching ratios of B → X s γ and B s → µ + µ − . If these constraints are taken into account, the largest poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 23 publications
2
45
0
Order By: Relevance
“…Gray circles in figure 2 denote all possible bosonic loops. These 2-boson diagrams contain the socalled Barr-Zee diagrams, which have already been computed and intensively discussed in the literature [38,47,[55][56][57][58]. The 2-boson diagrams also contain self-energy type diagrams in which the external photon couples to the muon line.…”
Section: -Boson and 3-boson Diagramsmentioning
confidence: 94%
See 2 more Smart Citations
“…Gray circles in figure 2 denote all possible bosonic loops. These 2-boson diagrams contain the socalled Barr-Zee diagrams, which have already been computed and intensively discussed in the literature [38,47,[55][56][57][58]. The 2-boson diagrams also contain self-energy type diagrams in which the external photon couples to the muon line.…”
Section: -Boson and 3-boson Diagramsmentioning
confidence: 94%
“…In other models, such as the MSSM, several classes of two-loop contributions have been evaluated [54][55][56][57][58][59][60][61]. It has been found that each class can give rise to significant corrections, and an analysis of the remaining MSSM theory uncertainty has shown that the future experimental precision can only be matched by a complete two-loop computation [62,63].…”
Section: 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Higher order contributions have been computed in [55][56][57][58][59][60][61][62][63]. At 1 loop there are five main contributions that can be split into two classes of diagrams: chargino/sneutrino and neutralino/smuon contributions.…”
Section: The Relic Density and (G − 2) µ In The Mssmmentioning
confidence: 99%
“…At one-loop level, the supersymmetric contributions to a µ with a µ = 1 2 (g − 2) µ [123][124][125][126][127][128] originate from chargino-sneutrino and neutralino-smuon loops. Large contributions may come from neutralino-smuon loops when µ is large along with smaller slepton masses [129][130][131].…”
Section: Muon G −mentioning
confidence: 99%